Programmed cell death 1 inhibitor plus chemotherapy vs. chemotherapy in advanced drive-gene-negative non-small-cell lung cancer patients: A real-world study - Li, Ying; Yang, Peng; Zhou, Xiao; Yang, Xuefeng; Wu, Shijie (Frontiers in Surgery, 2022)
Objective: Programmed cell death 1 (PD-1) inhibitor is just on market in China for several years, which lacks sufficient domestic evidence regarding its application in lung cancer. Thus, this study intended to assess the treatment outcome and tolerance of PD-1 inhibitor plus chemotherapy in advanced, driver-gene-negative, non-squamous, non-small-cell lung cancer (NSCLC) patients in a real clinical setting. Methods: This retrospective cohort study analyzed 68 advanced driver-gene-negative non-squamous NSCLC patients, among which 38 cases received PD-1 inhibitor plus chemotherapy and 30 cases adopted chemotherapy alone. Disease control rate (DCR), objective response rate (ORR), progression-free survival (PFS), overall survival (OS), and adverse events were reviewed. Results: Generally, PD-1 inhibitor plus chemotherapy achieved a more satisfying ORR compared with chemotherapy alone (52.6% versus 30.0%, P=0.061), while the DCR was not varied between PD-1 inhibitor plus chemotherapy and chemotherapy (84.2% versus 73.3%, P=0.271). Patients receiving PD-1 inhibitor plus chemotherapy exhibited favorable PFS (median: 10.1 versus 7.1 months, P=0.040) and OS (median: 17.4 versus 13.9 months, P=0.049) than patients adopting chemotherapy. Additionally, after the adjustment by multivariable Cox’s analyses, PD-1 inhibitor plus chemotherapy (versus chemotherapy) could independently realize prolonged PFS (P=0.020) and OS (P=0.029). Moreover, the majority of adverse events were manageable; meanwhile, grade 3-4 adverse events included leukopenia (13.2%), neutropenia (13.2%), nausea and vomiting (7.9%), anemia (5.3%), elevated transaminase (5.3%), thrombopenia (2.6%), anorexia (2.6%), peripheral neuropathy (2.6%), and rash (2.6%). Conclusion: PD-1 inhibitor plus chemotherapy exhibits a better efficacy and equal tolerance compared with chemotherapy alone in advanced driver-gene-negative non-squamous NSCLC patients.